Six ways of experiencing information literacy in nursing: The findings of a phenomenographic study. (January 2015) - Forster, Marc
Summary Background Information literacy plays a vital role in evidence-based practice in nursing. However there is currently little evidence to show how being information literate is actually experienced by nurses and therefore information literacy educational interventions are not genuinely evidence-based. Are they promoting the appropriate knowledge and skills to help nurses find and use the research evidence they need? Objectives To investigate how being information literate is experienced by nurses. To use the insights obtained to develop a description of the parameters of information literacy in nursing, including those of its role and value in evidence-based practice. Design Phenomenography. Participants 41 UK nurses of varying experience, specialism and background. Methods Open-ended interviews. Results 7 contexts in which information literacy is experienced, were mapped out and 6 representative ways of being an information literate nurse, in increasing levels of depth and sophistication, were described. Conclusions These findings may form the basis of future evidence-based information literacy education programmes.